Making All Children Count: Teach For All and the Universalizing Appeal of Data - Friedrich, Daniel; Walter, Mia; Colmenares, Erica (Education Policy Analysis Archives, 2015)
In this paper, we argue that in order to bind Teach For All’s universal/izing statement of problems and solutions to the specificities and the special conditions of member programs’ local contexts, what is needed is a shared set of discursive practices, a way of bringing together the commonalities found in each country while separating the noise of particular politics and histories. That common set of discursive practices is shaped around the notion of data. This paper is structured as follows: First, we contextualize Teach for All by (briefly) juxtaposing the universal and specific elements of the network, including the organization’s mission, target population, its recruits (and recruiting tactics), vision, and its production of a particular kind of teacher. Then, we present the two competing, yet complementary, logics of data that are at play in Teach for All – the use of data itself and the notion of data speak – along with their underlying assumptions. We conclude by questioning the logics of this set of discursive practices, and outline our skepticism regarding how data is mobilized to produce particular subjectivities and objects.